Planning processes. : An introduction for geographers - Herington, John. (Cambridge : New York : Cambridge University Press, 1989)
This book deals with the planning of towns, cities and regions in Britain with special reference to government attitudes and policies. Emphasis is placed on helping students to understand the link between planning processes and the changes they observe in the city and countryside
Includes bibliographical references (p. 113-115) and index.
Keywords: Planning